Internship report: civic education In Ghana - May, Madison (My University, 2016)
This summer, I was employed by the National Commission for Civic Education in Agona Swedru, Ghana. The creation of the NCCE was written into the Constitution of Ghana, with the primary purpose of educating and encouraging the public to defend this Constitution at all times, against all forms of abuse and violation. I chose to work for the NCCE in Ghana this summer because it is considered a model for successful and stable democratic transition. Many other African countries’ transition to democracy has ended with corrupt elections and violence. Furthermore, 2016 is a presidential election year for Ghana, which is when the NCCE is responsible for public education to sensitize electorates about the voting procedure and their conduct before, during and after presidential and public elections. My primary responsibility was educating rural communities about democracy and voting procedure. I did this by hosting community forums and giving informal presentations at churches and schools. In addition, I was shadowing an Assemblyman of the Gomoa East District and sitting in on Assembly meetings. When not involved in either of these, I was tutoring English at elementary schools and coaching soccer for young girls, with the goal of promoting confidence. My independent project for this summer was a research project for the K-State University Honors Program. I completed a Ghana Case Study to look at the connection between religion and democracy, and how religious attitudes shape political attitudes and participation. Ghana is 71% Christian, 17.6% Muslim, and 5.2% Traditional Ghanaian religion. I implemented a plan to interview Ghanaians from each of the predominant faiths. Upon my return to K-State, I hope to use my experience to promote religious diversity and tolerance on campus. I hope to continue to build this research project to uncover patterns between civic participation in government, government stability, and religion. If progress can be made toward uncovering the source of Ghana’s transitional success, then that knowledge can be applied to other countries facing similar circumstances.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: May, M. (2016). Internship Report: Civic Education in Ghana. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Ghana; Democracy; Africa; Election; Grassroots; Education; Internship and Residency--Case Reports; Ghana; Democracy--Africa; Africa; Civic engagement (Education); Education--Ghana--Government policy; Reports